Cerebral Microhemorrhages in Children With Congenital Heart Disease: Prevalence, Risk Factors, and Association With Neurodevelopmental Outcomes - Kristen N. Andersen; Sicong Yao; Brian R. White; Marin Jacobwitz; Jake Breimann; Jharna Jahnavi; Alexander Schmidt; Wesley B. Baker; Tiffany S. Ko; J. William Gaynor; Arastoo Vossough; Rui Xiao; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Infants with congenital heart disease require early lifesaving heart surgery, which increases risk for brain injury and neurodevelopmental delay. Cerebral microhemorrhages (CMH) are frequently seen after surgery, but whether they are benign or constitute injury is unknown. Methods and Results One hundred ninety‐two infants with congenital heart disease undergoing cardiac surgery with cardiopulmonary bypass were evaluated with pre‐ (n=183) and/or postoperative (n=162) magnetic resonance imaging. Perioperative risk factors for CMH and neurodevelopmental outcomes were analyzed using linear regression. Eighteen‐month neurodevelopmental outcomes were assessed in a subset of patients (n=82). The most common congenital heart disease subtypes were hypoplastic left heart syndrome (37%) and transposition of the great arteries (33%). Forty‐two infants (23%) had CMH present on magnetic resonance imaging presurgery and 137 infants (85%) postsurgery. We found no significant risk factors for preoperative CMH. In multivariable analysis, neurodevelopmental duration (P<0.0001), use of extracorporeal membrane oxygenation support (P<0.0005), postoperative seizure(s) (P=0.02), and lower birth weight (P=0.03) were associated with new or worsened CMH postoperatively. A higher CMH number was associated with lower motor scores (P=0.01) at 18 months. Conclusions CMH are common imaging findings in infants with congenital heart disease, particularly after cardiopulmonary bypass conferring adverse impact on neurodevelopmental outcomes at 18 months. Longer duration of cardiopulmonary bypass and extracorporeal membrane oxygenation use demonstrated greatest risk for developing CMH. However, the presence of CMH on preoperative scans indicates yet unidentified nonperioperative risk factors. Neuroprotective strategies to mitigate CMH risk may improve neurodevelopmental outcomes in this vulnerable population.